A closer look at willingness to pay: An economic perspective on the Gringsing weaving cultural industry - Dewi, Desak Made Marysha; Saskara, Ida Ayu Nyoman (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
Gringsing weaving from Tenganan Village is renowned for its distinctive indigo blue dye, derived from the tawum tree. However, traditional awig-awig (customary regulations) prohibit dyeing within the village due to environmental concerns, particularly the risk of groundwater contamination. As a result, dyeing activities are relocated to neighboring Bugbug Village, where local rivers are used for washing and saltwater soaking—processes that enhance the quality of the dye. This relocation has led weavers to outsource dyeing services, prompting an investigation into the factors influencing their willingness-to-pay (WTP). This study employs Focus Group Discussions (FGDs) with Gringsing weavers and relevant government stakeholders, supported by MICMAC (Matrix of Cross-Impact Multiplications Applied to a Classification) and Bayesian Belief Network (BBN) analyses. The MICMAC results identify cultural capital and awig-awig as primary driving factors shaping WTP. BBN analysis further highlights the significant influence of Communal Intellectual Property Rights (CIPR) and income stability. These findings suggest that willingness to pay is shaped not only by economic considerations but also by deeply embedded cultural and institutional factors. To ensure the long-term sustainability of the Gringsing weaving tradition, interventions must integrate cultural revitalization, environmental responsibility, and financial empowerment. Strengthening intellectual property protections, promoting income-generating opportunities, and respecting traditional regulatory frameworks are essential to preserving both the cultural integrity and economic viability of the Gringsing weaving industry.